(untitled) (Polish Yearbook of International Law, 2021)
It is not common for a judge in office at the World Court to publish a book on important subject of international law. But judge antonio augusto Cançado trindade is widely recognized as an outstanding and eminent defender of individuals and human rights in the contemporary international society. To this end, he successfully undertook a challenging venture to publish a book with all the bearing of a system of international law, a treatise, which was a significant attempt at reinstating the whole corpus juris as an obligatory, normative framework of contemporary international community in the years to come.